2017
DOI: 10.1080/19336896.2017.1300740
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a new 20-bp insertion/deletion (indel) within sheep PRND gene using mathematical expectation (ME) method

Abstract: Prion-related protein doppel gene (PRND), as an essential member of the mammalian prion gene family, is associated with the scrapie susceptibility as well as phenotype traits, so the genetic variation of the PRND has been highly concerned recently, including the single nucleiotide polymorphism (SNP) and insertion/deletion (indel). Therefore, the objective of present study was to examine the possible indel variants by mathematical expectation (ME) detection method as well as explore its associations with phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…On the other hand, the previous studies had reported that the resistant PRNP and PRND polymorphisms had different effects on growth and reproduction traits in different breeds (Lan, Zhao, Li, et al 2012;Ibrahim et al 2015;Yang et al 2016;Li et al 2017). However, the detailed associations between the PRNP polymorphisms and other economical traits remain elusive in cattle.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the previous studies had reported that the resistant PRNP and PRND polymorphisms had different effects on growth and reproduction traits in different breeds (Lan, Zhao, Li, et al 2012;Ibrahim et al 2015;Yang et al 2016;Li et al 2017). However, the detailed associations between the PRNP polymorphisms and other economical traits remain elusive in cattle.…”
Section: Discussionmentioning
confidence: 97%
“…The prion protein (PrP) which is encoded by prion protein gene (PRNP) plays an important role in the transmissible spongiform encephalopathies which include the bovine spongiform encephalopathy (BSE) (Zhu et al 2011;Zhao et al 2015), caprine (Curcio et al 2016) and ovine scrapie (Dassanayake et al 2013;Li et al 2017). The characteristic of TSE is the accumulation of PrP sc (pathological protease-resistant isoform), which is generated as a result of post-translational modification and changed in the stereochemical conformation of host-encoded, cellular prion proteins (PrP c ) (Prusiner 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The breed is now in peril of extinction because of human activity, climatic variation and destruction of its natural habitat (Li et al . , ). The fat tail, a valuable energy reserve characteristic of this breed, is considered an adaptive response to the harsh challenges of desert life and severe winters when pasture is scarce (Atti et al .…”
Section: Number Of Snps Identified From Three Sheep Breeds Using Rna‐mentioning
confidence: 99%
“…Moreover, previous work developed by our group [6] identified significant associations between novel 20 bp insertion/deletion (indel) polymorphisms in PRND with the cannon circumference index and trunk index in Chinese Hu sheep. Moreover, considering the linkage of PRND and its homologous gene, PRNP [7][8], our previous work also explored high rate of polymorphic mutations in PRNP and whether these were correlated with growth traits in Chinese cattle [9][10] or native sheep [11].…”
Section: Introductionmentioning
confidence: 88%
“…gov/Blast.cgi). The PCR reaction volume and amplification procedure were in accordance with our previous study [6,18]: initial denaturation for 4 min at 95 C, followed by 18 cycles of denaturation for 30 s at 94 C, annealing for 30 s at 68 C (with a reduction of 1 C per cycle), and extension for 1000 bp/min at 72 C, followed by another 23 cycles of 30 s at 94 C, 30 s at 50 C, and 45 s at 72 C, and a final extension of 10 min at 72 C. After cooling to 4 C, all PCR products were detected by 1.5% agarose gel electrophoresis and directly sequenced by Sangon Company (Shanghai, China). Finally all individuals were genotyped [19].…”
Section: Novel Snp Discovery and Genotyping By Direct Sequencingmentioning
confidence: 99%